2019
DOI: 10.1016/j.celrep.2019.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pluripotent Stem Cells from Mouse Embryonic Fibroblasts by Jdp2-Jhdm1b-Mkk6-Glis1-Nanog-Essrb-Sall4

Abstract: Highlights d Jdp2, Jhdm1b, Mkk6, Glis1, Nanog, Esrrb, and Sall4 (7F) convert MEFs into iPSCs d RNA-seq and ATAC-seq reveal a distinct path for 7F reprogramming d 7F cooperate to open and close chromatin during 7F reprogramming d 7F activate a TF network to induce pluripotency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…TF signatures of PF-NSC-like cells included JUN , FOS , and ATF3 , all of which are also top signature genes of this subpopulation ( Figure 2 E). Other TF regulons with high activity in PF-NSC-like cells were SRF and JDP2 , both of which are implicated in repression of cell differentiation and pluripotency induction ( Figure 2 E) ( Wang et al., 2019a ; Ikeda et al., 2018 ). The PF-Neuronal-Precursor-like program also showed a selective TF signature including NEUROG1/2 and ARID3A ( Figure 2 E), described to regulate neurogenesis ( Han et al., 2018 ) and promote oncogenic stemness ( Dausinas et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…TF signatures of PF-NSC-like cells included JUN , FOS , and ATF3 , all of which are also top signature genes of this subpopulation ( Figure 2 E). Other TF regulons with high activity in PF-NSC-like cells were SRF and JDP2 , both of which are implicated in repression of cell differentiation and pluripotency induction ( Figure 2 E) ( Wang et al., 2019a ; Ikeda et al., 2018 ). The PF-Neuronal-Precursor-like program also showed a selective TF signature including NEUROG1/2 and ARID3A ( Figure 2 E), described to regulate neurogenesis ( Han et al., 2018 ) and promote oncogenic stemness ( Dausinas et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The above analysis has revealed the well-ordered dynamic expression of TEs in developmental processes, we then wondered if TEs undergo similar stage-specific regulation during somatic reprogramming. Somatic cells can be reprogrammed to induced pluripotent stem cells (iPSCs) by various methods, such as ectopic expression of a group of pluripotency transcription factors 25,46,47 , or cocktails of chemicals 48,49 . The reprogramming process is highly heterogeneous, with abundant non-reprogramming cells and divergent cell fate transition routes 25,50 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SP8 was shown to enhance the recruitment of β-catenin, a co-activator that stimulates the expression of Wnt target genes 36 . Of note, SP8 has recently been identified as a downstream target which is activated by Nanog at day 5 of reprogramming 37 . This upregulation of SP8 was consistent with our data that showed that the SP8 gene stays upregulated through reprogramming and selfrenewal stages (passage 8).…”
Section: Discussionmentioning
confidence: 99%